Paperback “Haohan” and Other ‘Genred Genders’: Negotiated Masculinities among Chinese Popular Fiction Readers - Kozar, Seana (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1997)
This article examines the ways in which martial-arts and romance novel fans construct negotiated readings of masculinity through their interprrtations of two distinctive male character types common in Chinese vernacular fiction, the hero (haohan) and the talented scholar (caizï). Drawing on the concept of “hegemonic masculinities” (Comwall and Lindsfame 1994), the author examines how the hero and the scholar are historically juxtaposed across their respective genres, as well as how their attributes serve to highlight, complement, or challenge social constructions of gender in the minds of some readers. Also examined are readers’ perceptions about such key issues as reading for escape and/or compensation, identification and the phenomenon of reading addictions.